Local Cheese: Factors Affecting Consumption and PLS-Path Modelling Study - Tankosić, JV; Ignjatijević, S; Ivaniš, M; Mihajlović, M; Avakumović, J; Puvača, N (Journal of the Hellenic Veterinary Medical Society, 2024)
This paper proposes a model for investigating the current preferences of local cheese consumers in terms of the extrinsic and intrinsic quality attributes associated with the local cheese consumption awareness and the willingness to pay for local cheese in the Republic of Serbia. Local cheese extrinsic quality attributes such as adequate price, country of origin, geographical indication, and attractiveness of the label, have shown the strongest direct influence on the willingness to pay for local cheese. Strong influence is also manifested in the perceived extrinsic quality attributes of local cheese on the consumers‘ awareness of local cheese consumption. The intrinsic quality attributes of local cheese have a positive impact on the local cheese consumption awareness, but not on the willingness to pay more for local cheese, which shows that the intrinsic qualities of local cheeses should be further promoted in order to enhance the willingness to pay more for the local cheese in a specific location. The local cheese consumption awareness has manifested a direct positive relation with the willingness to pay for local cheese therefore the increased awareness of the importance of the consumption of local cheese can be reflected in stronger buying intentions. These insights can offer opportunities for strategic actions of local cheese market stakeholders regarding the local cheese promotion and consumption.